2012
DOI: 10.1007/978-3-642-25926-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Formalization and Data Enrichment for Automated Evaluation of Building Pattern Preservation

Abstract: ABSTRACT:Automated evaluation of generalization output relies to a large extent on that requirements (e.g. specifications, constraints) being formalized in machine-readable formats. Previous studies suggest that the formalization and automated evaluation are relatively easier for legibility constraints (improve the readability of maps) than for preservation constraints (preserving important real-world phenomena). Three major difficulties, i.e., pattern classification and characterization, pattern matching, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Also noted that another work on the automated evaluation of building pattern preservation constraint (Zhang et al, 2010) is carrying out based on the detection results reported in this paper.…”
Section: Discussionmentioning
confidence: 90%
“…Also noted that another work on the automated evaluation of building pattern preservation constraint (Zhang et al, 2010) is carrying out based on the detection results reported in this paper.…”
Section: Discussionmentioning
confidence: 90%
“…Experiments show that such an approach allows evaluating individually every element of the user's needs, the cartographic rules and even the respect of the initial data [4]. Nevertheless, difficulties remain in the evaluation of characters of complex group of objects like building alignments [9]. Although it allows a fine description of the legibility of a generalized map, the previous approach only provides the building blocks for a global evaluation of the map.…”
Section: Related Workmentioning
confidence: 99%
“…Better rules are required to replace Rule 2 in order to distinguish incorrect correspondence and potential n-to-m relationships. A prior matching of building groups as described in Zhang et al (2010) may be helpful.…”
Section: Classification Accuracymentioning
confidence: 99%